DOES RELIGIOSITY INFLUENCE THE RELATIONSHIP BETWEEN EMOTIONAL FACTORS AND WORKPLACE DEVIANT BEHAVIOUR? - Dora, Mohd Taib; Mohamed Azim, Abdul Mutalib (Journal of Human Capital Development (JHCD), 2019)
Drawing from social control theory, this study tested a moderating influence of religiosity in which emotional exhaustion and emotional stability as predictors and workplace deviance behavior is the outcome. Using data from 350 employees from the multimedia organization in Malaysia, we conducted Structural Equation Modelling analysis. Results found a positive and significant relationship between emotional exhaustion and workplace deviance behavior and negative impact of emotional stability towards workplace deviance behavior. Finally, religiosity moderates the relationship between emotional exhaustion and workplace deviance behavior, and religiosity moderates the relationship between emotional stability and workplace deviance behavior. The study makes a significant and unique contribution to the literature by showing the moderating influence of religiosity in the relationship between emotional exhaustion, emotional stability, and workplace deviance behavior. This study suggested that the employee with strong religious, mayreduce emotional exhaustion and enhance employee emotional stability, and thus, mitigate employee to engage in workplace deviance behavior. Keywords: religiosity, emotional exhaustion, emotional stability, workplace deviant behavior